A "cultural diplomatic machine" of the French Fourth Republic in Brazil - Suppo, Hugo Rogelio (2017)
Analysis of historical and political determinations that guided the assembly of a new cultural diplomacy for Latin America and Brazil in particular, over the period of the French Fourth Republic. France, in decline, is based initially on their previous cultural prestige to try to reposition itself in the world. However, soon realizes that it is necessary to build another image of herself, inspired by the success of the American model.